7 - Pour une stratégie alternative de développement. L’industrialisation au service de l’agriculture: Une Critique de la Stratégie du CILSS et du Club du Sahel. - Amin, Samir (Africa Development, 1981)
This paper tries to look into the strategy for food self -sufficiency for the Sahelian countries . Thus it considers critically the programmes proposed by the CILLS (an interstate Agency for the region) and the Club du Sahel (a Club of donors ), the target of which is to achieve food self- sufficiency around year 2000. Towards that goal , agricultural actions are defined for both dry farming and irrigation , cattle and forestry , and estimation of the volume of aid needed is made. The main conclusion of the author is that those programmes , by considering only agriculture, and not the global policies, lack consistency. Priority to food sufficiency is not synonymous to priority to «agricultural projects» and is a further delay in industrialisation. It is not a priority to type of industrialisation able to provide agriculture with the needed inputs. Parallel development of agriculture and industry is an absolute necessity, but not «any type of industrialisation» can provide a surplus for the modernisation of agriculture. Import substitution industry and export- oriented industry , in the framework of the international division of labour must be substituted by an industrialisation servicing the priority for agricul- ture. Ignorance of this fundamental point, which is also the case for the Inst report of the World Bank for Africa, reflects the prejudice against any reappraisal of the negative effects of so called «interdependence» and the will to continue global policies in this framework. It cannot but lead to wishful thinking, with a very high probability of not achieving the target food self-sufficiency. Samir AMIN, Directeur Projet de l'UNITAR : « Stratégies pour le Futur de l'Afrique», s/c CODESRIA, BP. 3304, Dakar, Sénégal